Menciptakan Usaha Baru Melalui Pelatihan Pembuatan Tempat Sampah Dan Pot Bunga Dari Galon Bekas Di Kelurahan Ngadirejo - Lilis Nurhalizah; Lia Nirawati (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Trash is a problem that will not run out. The solution to this situation must be creativity and innovation from the community to carry out waste processing so that it can be used as a new business opportunity. In Ngadirejo Village, there are lots of used gallons of waste that are not used, so I took the initiative to provide training on turning gallons into trash cans and flower pots with the creativity of the participants. This activity aims to care for the environment and can increase the economic income of the people of Ngadirejo Village, Blitar City. This training uses empowerment and practice methods. With the stages of the method, namely, first debriefing, second training, third discussion and fourth evaluation. The result of this activity is that the participants bring home their works in the form of trash bins and flower pots so that the participants are proud of the work they have made. It is hoped that this activity will benefit the community and the knowledge gained can be applied as a new business in Ngadirejo Village, Blitar City.